2009
DOI: 10.1007/s00253-009-2221-3
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of cyclodextrin glucanotransferases and the impact for biotechnological applications

Abstract: Cyclodextrin glucanotransferases (CGTases) are industrially important enzymes that produce cyclic α-(1,4)-linked oligosaccharides (cyclodextrins) from starch. Cyclodextrin glucanotransferases are also applied as catalysts in the synthesis of glycosylated molecules and can act as antistaling agents in the baking industry. To improve the performance of CGTases in these various applications, protein engineers are screening for CGTase variants with higher product yields, improved CD size specificity, etc. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
112
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 150 publications
(127 reference statements)
1
112
0
5
Order By: Relevance
“…The major activities of these enzymes are intramolecular (cyclization) and intermolecular (disproportion, coupling) transglycosylation (Kuo et al 2009). They are able to convert starch into cyclic α-1,4-glucans, called cyclodextrins (CDs) (Leemhuis et al 2010). CDs can accommodate various organic and inorganic molecules within the hydrophobic central cavity leading to changes in the chemical and physical properties of the guest molecules (Li et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The major activities of these enzymes are intramolecular (cyclization) and intermolecular (disproportion, coupling) transglycosylation (Kuo et al 2009). They are able to convert starch into cyclic α-1,4-glucans, called cyclodextrins (CDs) (Leemhuis et al 2010). CDs can accommodate various organic and inorganic molecules within the hydrophobic central cavity leading to changes in the chemical and physical properties of the guest molecules (Li et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Screening organic solvent-tolerant bacteria or extremophiles has been preferred to isolate and improve naturally solvent-stable enzymes (Gupta & Khare, 2009;Doukyu & Ogino, 2010). Other protein engineering examples with industrially and/or pharmacologically important enzymes include studies on cholesterol oxidase (Pollegioni et al, 2009), cyclodextrin glucanotransferases (Leemhuis et al, 2010), human butyrylcholinesterase (Masson et al, 2009), microbial glucoamylases (Kumar & Satyanarayana, 2009), lipases of different origins (Akoh et al, 2004;Verma et al, 2008;Kurtovic et al, 2009), phospholipases (Song et al, 2005;De Maria et al, 2007;Simockova & Griac, 2009) and phytases (Rao et al, 2009). Studies on extremozymes, enzymes isolated from extremophilic species, revealed their different structural and functional characteristics which could be exploited for biotechnological applications and improved further by protein engineering (Bjarnason et al, 1993;Hough & Danson, 1999;Georlette et al, 2004).…”
Section: Applications With Various Industrially Important Enzymesmentioning
confidence: 99%
“…They are extracellular induced enzymes produced by microbial cells, predominantly Bacillus species. However, production by a variety of other bacterial species has also been reported (Leemhuis et al, 2010). CGTase catalyzes mainly transglycosylation reactions (cyclization, coupling and disproportionation) but can also exhibit, to a lesser extent, α-amylase-like activity, hydrolyzing starch into short linear saccharides.…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports on the purification of CGTase enzymes, with most strategies used mainly involving adsorption of CGTase on starch followed by gel filtration. At present, CGTases from at least 50 host organisms have been identified and (partly) characterized, even though the genes for some have not been identified and sequenced yet (Leemhuis et al, 2010;Ramli et al, 2011). Most of the reported CGTases are monomeric, with those from Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%